EEG rhythms and retinal morphometric parameters before and after conventional therapy with adjunctive neuroprotective agent for refractive amblyopia and strabismic amblyopia (Ukrainian Journal of Ophthalmology, 2025)
Background: It has been suggested that the results of traditional pleoptic and orthoptic therapy for amblyopia may be improved by the adjunctive use of neuroprotective agents. Citicoline, a cholinergic and neuroprotective agent, is worthy of attention in this connection. The degree of maturation of the cortical structures can be assessed by electroencephalography (EEG), whereas retinal morphometric parameters, by optical coherence tomography (OCT). Consequently, alpha, beta, delta and theta percent times in the EEG record and OCT-based retinal morphometric parameters may be considered as a potential criterion for assessing the efficacy of treatment for amblyopia.Purpose: To assess EEG rhythms and OCT-based retinal morphometric parameters when using the neuroprotective agent citicoline as an adjunct to treatment for refractive and strabismic amblyopia.Material and Methods: Seventy-nine amblyopic children (158 eyes) aged between 4 and 12 years (were involved in the study. They were divided into a main group of 57 patients treated with conventional therapy plus citicoline eye drops and a control group of 22 patients treated with conventional therapy only. OCT was performed using Stratus OCT 3000 (Carl Zeiss Meditec Inc.) to assess optic disc parameters and retinal nerve fiber layer (RNFL) thickness. The international 10–20 system of electrode placement was employed to perform EEG using an EEG machine (Medicor EEY8S) and a 16-channel computer QUATTOR system (Kharkiv, Ukraine). Patients of the main group were treated with citicoline and vitamin B12 eye drops (OMK2®, one drop thrice daily) as an adjunct to the pleoptic and orthoptic treatment and a month on completion of the pleoptic and orthoptic treatment. This treatment was performed twice a year with a 3-4-month interval between courses.Results: The mean improvement in visual acuity in the amblyopic eye was 0.4 ± 0.16 in the main group versus 0.2 ± 0.1 in the control group. In addition, contrast sensitivity score improved more substantially (from 1.5±0.7 to 2.8±0.4) in the former than in the latter group (from 1.5±0.7 to 2.8±0.4 points). After treatment, the OCT-based temporal RNFL thickness in the main group increased significantly from 72.5±14.6 µm to 78.5±22.0 µm. In addition, alpha indices increased to normal values in 73% of children with refractive amblyopia, and in 55% of children with strabismic amblyopia, of the main group, versus 54% and 60%, respectively, for the control group. Moreover, delta and theta indices reduced to 58±9.6% and 7.8±6.7% in 54% and 60%, respectively, of children of the former group, versus 41.7% and 50%, for the latter group.Therefore, when used as an adjunct to the comprehensive therapy for amblyopia, the neuroprotective agent can improve visual functions and rhythm indices related to EEG rhythms, which facilitates the development of the visual system in this pathology.
Keywords: amblyopia; OCT of the retina and optic disc; electroencelography; treatment; neuroprotective agent